2020
DOI: 10.3855/jidc.12189
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance pattern of Escherichia coli isolates from outpatients with urinary tract infections in Somalia

Abstract: Introduction: Several studies suggest increasing rates of antibiotic resistance among adult populations with Urinary tract infections (UTI). Escherichia coli (E. coli), is the predominant bacterium both in the community and in hospital environments causing uropathogenic infections. This study aimed to estimate the common uropathogen bacteria that cause UTI among outpatients as well as to determine the antibiotic resistance pattern of E. coli isolates among outpatients with UTI infections at Shaafi hospital, Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
2
10
2
1
Order By: Relevance
“…In general, the penicillins and cephalosporins are not active against UTIs in developing countries, such as Iraq; therefore, according to the results, such antibiotics should not be used in the treatment of UTIs. In recent years, quinolones, es-pecially ciprofloxacin, have been used to treat E. coli infections, and studies in different parts of the world have shown that quinolones are still active against UTIs (23,24). However, 27% of the UPEC isolates in the present study showed resistance to ciprofloxacin.…”
Section: Discussioncontrasting
confidence: 49%
“…In general, the penicillins and cephalosporins are not active against UTIs in developing countries, such as Iraq; therefore, according to the results, such antibiotics should not be used in the treatment of UTIs. In recent years, quinolones, es-pecially ciprofloxacin, have been used to treat E. coli infections, and studies in different parts of the world have shown that quinolones are still active against UTIs (23,24). However, 27% of the UPEC isolates in the present study showed resistance to ciprofloxacin.…”
Section: Discussioncontrasting
confidence: 49%
“… 17 , 18 Previous studies in Iran, Sudan, and Somalia have all reported a high rate of bacterial contamination among patients under hospitalization, which conforms with the result of the present study. 12 , 13 , 19 In each of the aforementioned reports, the poor healthcare delivery services, and poverty may have played a role in the high rate of bacterial isolation observed.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined using the 26.5% prevalence of Staphylococcus aureus reported by Mohammed et al among outpatients with urinary tract infections in Somalia. 13 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Isso ocorreu, também, devido ao uso descontrolado e indevido de antibióticos 3 , além disso, pacientes não hospitalizados com infecção urinária têm apresentado alto risco em desenvolver resistência aos antibióticos. 4 Como consequência da RAM, muitos dos medicamentos geralmente utilizados na terapêutica não apresentam eficácia e as infecções permanecem no hospedeiro tendendo a uma ameaça de proliferação. 5 O uso indiscriminado dos antimicrobianos amplia a pressão seletiva e beneficia o progresso da resistência, pois muitos pacientes acabam se automedicando além de não cumprir com o tratamento corretamente.…”
Section: Introductionunclassified